A Conceptual Model of Leisure Time Physical Activity, Neighborhood Environment, and Sense of Community. Issue 6 (June 2019) - Ross, Allison; Searle, Mark
The relationship between leisure time physical activity (LTPA) behaviors and the neighborhood environment (NE) has become a prominent research topic. This research investigates the complex relationship between LTPA and NE while also investigating their association with sense of community (SOC). Using data from a sample of 625 adults in the Greater Phoenix Metro area (AZ), a conceptual model is introduced to examine the relationships between LTPA, NE, and SOC while controlling for demographic, sociocultural, and community characteristics. Results of a structural equation modeling analysis indicate that LTPA was positively associated with SOC, NE was positively associated with LTPA, and NE was positively associated with SOC. These findings support future interventions that focus on features of NE when promoting LTPA behaviors and building SOC within the neighborhood. Furthermore, the simultaneous measurement of these constructs offers insight into the dynamic relationships that exist, informing future research and programming efforts.